2017
DOI: 10.18203/2320-1770.ijrcog20175827
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Carbetocin to decrease blood loss during open myomectomy: a randomized placebo-controlled study

Abstract: Background: Uterine leiomyomas are benign tumors of the uterus, which represent the most common neoplasms in women of reproductive age, and have a lifetime incidence of approximately 70% in the general population. The objective of this study was to assess the effect of using a single pre-operative dose of IV 100 μg Carbetocin on intraoperative blood loss in abdominal myomectomy surgeries. Methods: In a randomized double-blind placebo-controlled trial, 86 women undergoing abdominal myomectomy for symptomatic ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 14 publications
(19 reference statements)
4
10
1
Order By: Relevance
“…In agreement with our results, Sallam et al [19] reported that there was high significant reduction in intraoperative blood loss in Carbetocin group (714.19 ±186.27) compared with placebo group (1033.49 ± 140.9) (P=0.0001). The mean blood loss in the placebo group was 1033mL and 714 mL in the study group.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our results, Sallam et al [19] reported that there was high significant reduction in intraoperative blood loss in Carbetocin group (714.19 ±186.27) compared with placebo group (1033.49 ± 140.9) (P=0.0001). The mean blood loss in the placebo group was 1033mL and 714 mL in the study group.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with the present study, Yang and colleagues, 2012 [14], as well as others [15,16] compared Carbetocin and oxytocin in decreasing blood loss during laparoscopic myomectomy and concluded that giving Carbetocin pre-operatively to laparoscopic myomectomy patients had good clinical efficacy [14]. reduced total blood loss, yet haemoglobin decline and transfusion requirements were noted [17].…”
Section: Discussionsupporting
confidence: 86%
“…Sallam and Shady [11] results showed that intraoperative blood loss was significantly lower in those women randomized to receive IV carbetocin versus the placebo group (714.19 ± 186.27 ml versus 1033.49 ± 140.9 ml), (p = 0.0001). Also, the incidence of blood transfusion was increased in placebo group (69.8%) compared with (18.6%) in carbetocin group, (P = 0.0001) and there was a significant reduction in operative time in carbetocin group (66.35% ± 10.18) compared with placebo group (95.95 ± 9.16), (P = 0.0001).…”
Section: Discussionmentioning
confidence: 95%
“…The results of the present study in carbetocin patients (group 2) revealed that there were highly statistical significant differences between both levels of hemoglobin and HCT before and after myomectomy groups (P<0.001 for both). Sallam and Shady [11] carried out a randomized double-blind placebo controlled trial included 86 women undergoing abdominal myomectomy for symptomatic uterine leiomyomas who were randomly assigned to receive a single dose of pre-operative of IV 100μg carbetocin (n = 43) or placebo (n = 43) just before the operation. The results showed that when comparing the pre-operative and postoperative hemoglobin and as secondary outcomes observing the change in hemoglobin and was lower in the study group but not reach statistical significance (P > 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation